2022
DOI: 10.30773/pi.2022.0151
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the Delirium Diagnostic Tool-Provisional (K-DDT-Pro)

Abstract: Objective The Delirium Diagnostic Tool-Provisional (DDT-Pro) was designed to detect the presence and severity of delirium briefly and objectively regardless of psychiatric expertise. We translated the DDT-Pro into Korean and validated it in elderly Korean patients.Methods To validate the translation and evaluate inter-rater reliability, a psychiatric trainee and a research nurse independently assessed the same patients referred to the Department of Psychiatry. The results were compared with the reference evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…The scores range from 9 points (best performance) to 0 (worst performance). Kim et al [ 63 ] translated the DDT-Pro into Korean and validated it in psychiatric setting. The DDT-Pro cutoff scores ≤ 6 and ≤ 7 have been shown to balance sensitivity and specificity in detecting delirium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scores range from 9 points (best performance) to 0 (worst performance). Kim et al [ 63 ] translated the DDT-Pro into Korean and validated it in psychiatric setting. The DDT-Pro cutoff scores ≤ 6 and ≤ 7 have been shown to balance sensitivity and specificity in detecting delirium.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, arousal is usually not impaired in patients with dementia, even in the advanced stages, but appears to be a specific indicator of delirium; arousal level assessment has shown promise for screening delirium superimposed on dementia (DSD). Additionally, Kim et al [ 63 ] validated the predictive value of DDT-Pro for delirium among patients referred to the department of psychiatry, which showed that DDT-Pro appeared to be satisfactory in identifying delirium and its subtype. The sensitivity and specificity of psychiatrist evaluation of delirium were higher at a cutoff value of 6 (84% and 94.1%) and 7 (100% and 82.4%) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation